The use of different dispersive Raman spectrometers for the analysis of uranium compounds - Ho Mer Lin, Doris; Fanghänel, Thomas (Vibrational spectroscopy, 2014)
The performances of three different Raman spectrometers were compared and evaluated as a suitable tool for the analysis of a range of uranium compounds with a view to application in nuclear forensics. These included uranium ore concentrates of different chemical composition and uranium dioxide in the form of powder and sintered fuel pellet. The three spectrometers are termed as ‘portable’ or ‘hand-held’ from Ahura Scientific (785nm), ‘Senterra’ from Bruker (532 and 785nm), ‘T64000′ from HORIBA Jobin Yvon (488.0, 514.5, 647.1 and 752.5nm). Figures of merit such as sensitivity, signal-to-noise ratio and detection capability were compared. The portable Raman displayed fairly good sensitivity and process related impurities could be detected despite the miniaturisation but it was unable to measure darkly coloured powders such as calcined ore concentrates or uranium dioxide powder. The bench-top spectrometer Senterra had the best sensitivity for all the seven measured uranium compounds and the best signal-to-noise ratio for six of the compounds. Laboratory T64000 had the best resolution and at the same time resulting in the poorest sensitivity among the three spectrometers for all compounds measured. However, T64000 has very low level of noise therefore leading to better signal-to-noise that were comparable, if not better than the portable or Senterra. All industrial compounds measured in this study could not be measured with higher frequency laser thus impeding the observation of N-H or O-H vibration bands, of which the latter could be observed with laboratory synthesized material.